The influence of the red tide phenomenon on human health and welfare / Nur Syawanie Abdul Aziz ... [et al.] - Abdul Aziz, Nur Syawanie; Jamaludin, Siti Nur Syifaa; Rahizar, Nurshahirah; Shukor, Siti Nur Shazwani; Abd Malek, Alyssa Safiyah; Hisham, Nur Hafizah; Noor Hisham, Aida Qasrina; Kamaruddin, Sharir Aizat; Hashim, Aimie Rifhan (Universiti Teknologi MARA, Negeri Sembilan, 2024)
A phenomenon known as "red tide" describes a natural occurrence in which a high concentration or bloom of particular forms of marine algae in coastal or marine waters. Image 1 shows the discovery of red tide algae in coastal waters around Kota Kinabalu and Tuaran. Although the phrase "red tide" refers to a reddish-brown staining of the water, it can also appear as brown, green, or even blue tides depending on the type of algae involved. Red tide is primarily caused by specific algae, such as dinoflagellates and diatoms, growing quickly in favourable climatic conditions. Among the many factors contributing to red tides is nutrient enrichment. The overabundance of nutrients in the water, such as phosphate and nitrogen, might encourage the growth of algae. Numerous sources, including sewage discharge, agricultural runoff as shown in Image 2, and natural phenomena like upwelling, can provide these nutrients. Besides that, plenty of harmful algal species favour warm water conditions.